2023
DOI: 10.4252/wjsc.v15.i5.385
|View full text |Cite
|
Sign up to set email alerts
|

Cell transplantation therapies for spinal cord injury focusing on bone marrow mesenchymal stem cells: Advances and challenges

Abstract: Spinal cord injury (SCI) is a devastating condition with complex pathological mechanisms that lead to sensory, motor, and autonomic dysfunction below the site of injury. To date, no effective therapy is available for the treatment of SCI. Recently, bone marrow-derived mesenchymal stem cells (BMMSCs) have been considered to be the most promising source for cellular therapies following SCI. The objective of the present review is to summarize the most recent insights into the cellular and molecular mechanism usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 129 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Bone-marrow-derived stem cells (BMDSCs) are multipotent stem cells that can differentiate into different functional cells. Due to their easy acquisition in adult bone marrow, these cells have emerged as an important candidate for stem cell therapy in various diseases [44][45][46]. In 2011, Nagori et al [47] reported a successful pregnancy in a patient with refractory intrauterine adhesions through the autologous transplantation of BMDSCs.…”
Section: Bmdscsmentioning
confidence: 99%
“…Bone-marrow-derived stem cells (BMDSCs) are multipotent stem cells that can differentiate into different functional cells. Due to their easy acquisition in adult bone marrow, these cells have emerged as an important candidate for stem cell therapy in various diseases [44][45][46]. In 2011, Nagori et al [47] reported a successful pregnancy in a patient with refractory intrauterine adhesions through the autologous transplantation of BMDSCs.…”
Section: Bmdscsmentioning
confidence: 99%